Penetration of topical diclofenac into synovial tissue and fluid of osteoarthritic knees: a multicenter, randomized, placebo-controlled, pharmacokinetic study. (August 2020) - Seefried, Lothar; Blyth, Mark; Maheshwari, Rohit; McDonnell, Stephen M.; Frappin, Guillaume; Hagen, Martina; Maybaum, Nadine; Moreira, Sebastian; Pandit, Hemant
Background: Topical diclofenac, a nonsteroidal anti-inflammatory drug, has proven efficacy and safety in the management of osteoarthritis pain. We investigated penetration of topical diclofenac into knee synovial tissue and fluid (primary objective) and evaluated relative exposure in the knee versus plasma (secondary objective). Methods: In this phase I, double-blind, multicenter study, patients scheduled for arthroplasty for end-stage knee osteoarthritis were randomly assigned 2:1 to 4 g diclofenac diethylamine 2.32% w/w gel (92.8 mg diclofenac diethylamine, equivalent to 74.4 mg diclofenac, per application) or placebo gel, applied to the affected knee by a trained nurse/designee every 12 h for 7 days before surgery. Diclofenac concentrations were measured in synovial tissue, synovial fluid and plasma from samples obtained during surgery ⩾12 h after last application. Treatment-emergent adverse events (TEAEs) were evaluated. Results: Evaluable synovial tissue or fluid samples were obtained from 45 (diclofenac n = 29; placebo n = 16) of 47 patients. All diclofenac-treated participants had measurable diclofenac concentrations in synovial tissue [geometric mean 1.57 (95% confidence interval (CI) 1.12, 2.20) ng/g] and fluid [geometric mean 2.27 (95% CI 1.87, 2.76) ng/ml] ⩾12 h after the last dose. Geometric mean (95% CI) ratio of diclofenac in synovial tissue:plasma was 0.32 (0.23, 0.45) and in synovial fluid:plasma was 0.46 (0.40, 0.54). TEAE rates were similar for diclofenac (55.2%) and placebo (58.8%); none were treatment related. Conclusions: Topical diclofenac diethylamine 2.32% w/w gel penetrated into the osteoarthritic knee after repeated application and remained detectable in synovial tissue and fluid at the end of the final 12 h dosing cycle.